2015
DOI: 10.4049/jimmunol.1403083
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase PP4 Negatively Regulates Type I IFN Production and Antiviral Innate Immunity by Dephosphorylating and Deactivating TBK1

Abstract: The effective recognition of viral infection and subsequent type I IFN production is essential for the host antiviral innate immune responses. The phosphorylation and activation of kinase TANK-binding kinase 1 (TBK1) plays crucial roles in the production of type I IFN mediated by TLR and retinoic acid–inducible gene I–like receptors. Type I IFN expression must be tightly regulated to prevent the development of immunopathological disorders. However, how the activated TBK1 is negatively regulated by phosphatases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…(28,30,(57)(58)(59)(60)(61)(62). For instance, protein phosphatase, Mg2 + /Mn2 + -dependent 1A and 1B, protein phosphatase 4, Raf kinase inhibitor protein, glycogen synthase kinase-3b, and glucocorticoids have been reported to modulate TBK1 activity through phosphorylation and dephosphorylation (63)(64)(65)(66)(67). The K63-linked polyubiquitination of TBK1 is associated with enhanced TBK1 activity and type I IFN signaling, The ubiquitin E3 ligases TRAF, mind bomb 1 and 2, neuregulin receptor degradation protein-1, and ring finger protein-128 promote the K63-linked polyubiquitination of TBK1 and boost the innate immune response (62,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…(28,30,(57)(58)(59)(60)(61)(62). For instance, protein phosphatase, Mg2 + /Mn2 + -dependent 1A and 1B, protein phosphatase 4, Raf kinase inhibitor protein, glycogen synthase kinase-3b, and glucocorticoids have been reported to modulate TBK1 activity through phosphorylation and dephosphorylation (63)(64)(65)(66)(67). The K63-linked polyubiquitination of TBK1 is associated with enhanced TBK1 activity and type I IFN signaling, The ubiquitin E3 ligases TRAF, mind bomb 1 and 2, neuregulin receptor degradation protein-1, and ring finger protein-128 promote the K63-linked polyubiquitination of TBK1 and boost the innate immune response (62,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research studied feedback regulation in TLRs signaling pathways, in which positive/negative feedback regulation controlled the expression of up/down-stream factors and regulated immune and inflammatory reactions (21-23). Imaizumi et al found that the positive feedback of IFN-stimulated gene56 regulated the expression of IFN-stimulated gene54 in the TLR3/IFN-β signaling pathway (23).…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine PP4 complex was recently identified as a requisite factor for proper immune responses in T cells, B cells, and macrophages, 40, 41, 42 including proliferation and immune gene induction. Although the specific role of PP4 in glial cell immunity has not been investigated, increased PP4 expression has been reported in glial tumors, suggesting a connection between PP4 function and glial cell invasiveness.…”
Section: Discussionmentioning
confidence: 99%